Development And Evaluation Of An Integrated Stem Through Engineering Design Module Towards Students’ Achievement, Critical Thinking Skill And Stem Career Interest - Goonasakaran, Sathisha (2020)
Current initiation of implementing STEM in Malaysia required effective instructional material that able to effect students’ achievement, critical thinking skill and STEM career interest. In line with that, this study had developed and evaluated an integrated science, technology, engineering and mathematic through engineering design process (iSTEM-EDP) module for the topic Nutrition that was intended for Form Four secondary school students. This module was developed based on Constructivism Theory, Situated Learning Theory and Social Cognitive Career Theory using ADDIE Model. The science and engineering practice and crosscutting concepts from NGSS fused into Malaysia’s National Curriculum for Form Four Biology to form an interdisciplinary learning using STEM through engineering design process. Upon developing and validating, the module was implemented in one of the school in Northern Region of Malaysia. The quasi experimental research design was used to conduct this study. The experimental group followed the iSTEM-EDP Module whereby the control group used conventional method to learn the topic Nutrition. The pre-test, post-test and delayed post-test was administered upon both groups using three instruments namely the Nutrition Test, Watson-Glaser Critical Thinking Appraisal and STEM Career Interest Survey.